2001
DOI: 10.1248/bpb.24.785
|View full text |Cite
|
Sign up to set email alerts
|

4-Acetyl-12,13-epoxyl-9-trichothecene-3,15-diol Isolated from the Fruiting Bodies of Isaria japonica YASUDA Induces Apoptosis of Human Leukemia Cells (HL-60).

Abstract: The fruiting bodies of Isaria fungi have been traditionally used in Korea to treat cancer. An apoptosis-inducing compound, 4-acetyl-12,13-epoxyl-9-trichothecene-3,15-diol, was isolated from the methanol extract of fruiting bodies of Isaria japonica YASUDA by bioassay-guided fractionation. The apoptosis of the human leukemia cells (HL-60) by the compound was accessed by propidium iodide-staining flow cytometric analysis, and apoptosis-inducing activity at IC 50 concentration (10 nmol/l) was further confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In addition, recent reports show apoptosis induced by exposure to FB1 (Seefelder et al, 2003) and other Fusarium toxins such as 4-acetyl-12,13-epoxyl-9-trichothecene-3,15-diol and fusarenone X (Miura et al, 2002;Oh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent reports show apoptosis induced by exposure to FB1 (Seefelder et al, 2003) and other Fusarium toxins such as 4-acetyl-12,13-epoxyl-9-trichothecene-3,15-diol and fusarenone X (Miura et al, 2002;Oh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H-1 H COSY correlations between H-C(7) and H-C(8) established the linkage of C(7) and C (8). The HMBC correlations from H-C(10) to C(8), C(9) and C (11), and from H-C(11) to C(8), C(9) and C(10) established the fragment of C(7) to C (12). The HMBC correlations from H-C(7) to C(2), and H-C(3) to C(7) determined the linkage between C(7) and C(2).…”
mentioning
confidence: 99%
“…These results showed that striguellone A had cytotoxic effects on HeLa cells and its antitumor action may be through apoptosis induction. In recent years, some natural products with the ability to induce apoptosis have been isolated from edible and medicinal fungi, such as trichothecene from Isaria japonica [12], grifolin from Albatrellus confluens [13], ergosterol peroxide from Sarcodon aspratus [14], orsellinaldehyde from Grifola frondosa [15], and clitocine from Leucopaxillus giganteus [16]. In this paper, we found that striguellone A from L. striguellus has apoptosisinducing activity on HeLa cells, which may be significant for promoting the discovery of antitumor prodrugs from edible or medicinal mushrooms.…”
mentioning
confidence: 99%
“…Besides cordycepin and polysaccharides (Yin et al 2007), a number of bioactive constituents have been reported from P. tenuipes. These include: tenuipesine A (Kikuchi et al 2004a), spirotenuipesine A and B (Kikuchi et al 2004b), paecilomycine A, B, and C (Kikuchi et al 2004c), 4b-acetoxyscirpene-3, 15-diol (Nam et al 2001;Oh et al 2001;Yoo et al 2005), ergosterol (Nam et al 2001), and beauvericin and its analogues (Nilanonta et al 2000(Nilanonta et al , 2002. Moreover, phthalic acid, stearic acid, di (2-ethylhexyl) phthalate, and cholesterol were also reported from this mushroom (Song et al 2007).…”
Section: Discussionmentioning
confidence: 76%